Kim są bydgoszczanie? (Kronika Bydgoska, 2018)
Never in the history of the city, in such a short period of time, there had been so significant changes in population structure like during the return of Bydgoszcz to the Homeland in 1920. In 1919-1921, almost all Germans left the city. Who were the Poles who had arrived here? Who are their descendants, present-day residents of Bydgoszcz? Kuyavians, Pomeranians or perhaps Wielkopolans? Analyses of the local settlers origins indicate that the vast majority of today’s residents of Bydgoszcz are the descendants of Wielkopolans. Geographers place Bydgoszcz in the borderland of Kuyavia, Krajna, Pałuki, Vistula Pomerania, and the Chełmno Land, but it is largely populated by Wielkopolans